A description on multiple intelligences employed by diploma students in UiTM Sarawak / Saira Joe, Amelia Alfred Tom and Rosline Sandai - Joe, Saira; Alfred Tom, Amelia; Sandai, Rosline (UiTM Shah Alam, Selangor, 2010)
Aligning students' intelligence with instruction is of upmost importance in improving their achievement. Realising such importance, the purpose of this study is to investigate and describe the patterns of the eight intelligences employ by diploma students in UiTM Sarawak based upon the Multiple Intelligence theory by Gardner. The study employed a survey research design involving 330 Part One Diploma students in Semester 1, 2008/2009. The participants comprised 124 (37.6%) males and 206 (62.4%) females. Survey questionnaires were used as the instrument of the study. The questionnaires were distributed to all Part One Diploma students in twelve faculties on week 12 of the semester. The questionnaires were monitored by lectures from Academy of Language studies who taught Consolidating Language Skills Bel 120. The results of the study revealed that the most employed intelligences as indicated by the students is logical-mathematical intelligence (mean=3.4806), followed by verbal-linguistic (mean=3.2021), bodily-kinesthetic (mean=3.0470) and Intrapersonal (mean=3.0212). The less employed intelligences as stated by the students are musical (mean=2.7355) and naturalist (mean=2.8529). The findings provide great significance in addressing what is lacking in the proficiency courses. The need to address students' multiple intelligence in the classroom is highlighted in the study as it could help enhance students' achievement in learning the target language. The outcome of this research provides crucial pedagogical implications for the consideration of student's multiple intelligence in English as a second language proficiency courses.